Efforts and outcomes of task shifting/sharing implemented by clinical laboratory technicians in emergency departments - NISHIO, Yuki; MORIMOTO, Chiho; ISOBE, Yuta; KOJIMA, Arisa; SUZUKI, Masahiro; MIYAMOTO, Kohei; ITO, Eiji; OHSHIMA, Takeshi (Japanese Journal of Medical Technology, 2025)
As the number of emergency patients increases nationwide, and the burden on doctors and nurses grows, task shifting/sharing to various professions is being promoted to ensure the sustainability of healthcare. In 2021, the scope of clinical laboratory technicians’ work was expanded, and their role in emergency settings became more expected. To achieve this, our hospital’s lab department has been working on streamlining and standardizing tasks since 2018 to improve workforce efficiency. After establishing a new group and training generalists, we began full-scale implementation with a permanent system in 2023. By handling newly expanded tasks due to legal reforms, as well as traditional tasks such as blood draws, ECGs, and specimen collection, we reduced the burden by approximately 1,005 hours annually. However, legal restrictions limit effective burden reduction in areas such as IV access and transfusion therapy. We believe that having clinical laboratory technicians permanently stationed in emergency departments improves workforce efficiency and deepens collaboration with other professions, contributing to the enhancement of emergency medical care quality.